Introducing sociolinguistics - Meyerhoff, Miriam (Routledge/Taylor & Francis Group, 2019)
"This third edition of Miriam Meyerhoff's highly successful textbook is supported by The Routledge Sociolinguistics Reader, Doing Sociolinguistics and online resources shared by all books. It provides a solid, up-to-date appreciation of the interdisciplinary nature of the field covering foundation issues, recent advances and current debates. It presents familiar or classic data in new ways, and supplements the familiar with fresh examples from a wide range of languages and social settings. It clearly explains the patterns and systems that underlie language variation in use, as well as the ways in which alternations between different language varieties index personal style, social power and national identity. New features of the third edition: every chapter revised and updated with current research in the field, including material on sexuality, polylanguaging, and lifespan change; additional Connections with theory and Facts: No really? throughout; revised and expanded data from signed languages, historical linguistics and Asia-Pacific sociolinguistics; brand new companion website featuring more examples and exercises at www.routledge.com/textbooks/meyerhoff. Chapters include exercises that enable readers to engage critically with the text, break-out boxes making connections between sociolinguistics and linguistic or social theory, and brief, lively add-ons guaranteed to make the book a memorable and enjoyable read. With a full glossary of terms and suggestions for further reading, this text gives students all the tools they need for an excellent command of sociolinguistics"--